Analisis Rantai Pasok Kopi Pada Kelompok Tani Kopi Rejo Di Desa Wisata Gombengsari Banyuwangi - Fenita Melinda; Adetiya Prananda Putra; Jemi Cahya Adi Wijaya (STIE Pariwisata API Yogyakarta, 2024)
The supply chain of the tourism industry and the creative economy is very closely related through efforts to develop industrial ecosystems including business partnerships from upstream to downstream. One of the culinary sub-sectors that is growing rapidly, and has even become a new lifestyle for the people, is Indonesian coffee. The increase in the amount of national coffee consumption is of course followed by the level of archipelago coffee production. Banyuwangi Regency has strategic coffee-producing locations, one of which is located in Gombengsari Village. This study aims to analyze the coffee supply chain in the Gombengsari Coffee and Tourism Village, so that the authors can determine the priority of development recommendations in order to improve the performance of coffee supply chain management in the Gombengsari Coffee and Tourism Village. The research method used is descriptive analysis using case study research techniques with data testing, namely using marketing analysis, marketing margins, farmer's share, and marketing efficiency. The results of this study indicate that there are three patterns of coffee flow. Farmers can apply partnerships and creative economy concepts to increase tourism development in the Gombengsari Coffee and Tourism Village, Banyuwangi Regency.